Exploration of microalgal culture using a semi-closed thin layer cascade photobioreactor for biodiesel synthesis and protein production - Tan, Chung Hong (2020)
The expanding aquaculture industry increases the prices of fishmeal, the main protein source in fish diet. A promising alternative is microalgal protein. Therefore, the protein production capacities of two green microalgae species, Chlorella sorokiniana CY1 and Chlorella vulgaris ESP-31, were investigated. After optimization, the maximum biomass and protein productivities of Chlorella sorokiniana CY1 reached high values of 4.35 ± 0.09 and 0.856 ± 0.025 g/L/d, while that of Chlorella vulgaris ESP-31 also reached high values of 4.636 ± 0.10 and 0.946 ± 0.065 g/L/d. The cultivation time for both species was only 2 days, wherein Chlorella sorokiniana CY1 and Chlorella vulgaris ESP-31 amassed moderate protein contents of 25.9 ± 1.3% and 26.8 ± 1.3%. The optimum conditions for both species were 50% initial nitrate concentration of Basal medium, 5% CO2 aeration, and 750 µmol/m2/s light intensity. The high biomass and protein productivities of both species indicated their capability as potential protein sources.